An Analysis of Gold Futures as an Alternative Asset: Evidence from India - Jaiswal, Ritika; Uchil, Rashmi (International Journal of Economics and Financial Issues, 2018)
This study incorporates the regime switching framework to investigate the hedge and safe haven property of gold futures against the stock and bond market movements. The Markov-Switching Vector Autoregression (MS-VAR) model is adopted, which splits the whole sample period into two extreme regimes. One of the regimes accounts for the period of high volatility in stock and bond returns and enables to verify the safe haven role of gold futures. Conversely, another regime represents the period of average stock returns and low volatility which allows to define the hedging potential of gold futures. The results demonstrate weak hedging potential of gold futures against the stock and bond market movements. However, during the financial turmoil and extreme market movements, gold futures cannot be used as a safe haven. In addition, portfolio analysis confirms that findings of MS-VAR are useful for investors and fund managers to get improved risk-adjusted return from the portfolio. The empirical findings nullify the conventional wisdom attached to the gold futures with respect to their safe haven property and have pervasive policy implication with respect to this. Keywords: Gold Futures, Hedge, Markov-Switching, Safe Haven JEL Classifications: G10, G11, G12, G13 DOI: https://doi.org/10.32479/ijefi.7346